2018
DOI: 10.14419/ijet.v7i2.3.12630
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Analysis of TOPSIS and Fuzzy Logic Methods On Fertilizer Selection

Abstract: Decision Support System is an interactive system that supports decision in the decision-making process through alternatives derived from the processing of data, information and design of the models. Selection decision support system of chemical fertilizer in fruit plant is expected to help anyone who wants to cultivate fruit trees can determine the chemical fertilizer as expected based alternatives and criteria set by the user. In this research method used is TOPSIS Method and Method of Fuzzy Logic. TOPSIS met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 19 publications
0
15
0
1
Order By: Relevance
“…Decision making in an organization is the result of a continuous process of communication and participation of the entire organization [10]. The issue of decision making is basically a form of selection of various alternative actions that may be selected for which the process is through a certain mechanism, with the hope that it will produce the best decision.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Decision making in an organization is the result of a continuous process of communication and participation of the entire organization [10]. The issue of decision making is basically a form of selection of various alternative actions that may be selected for which the process is through a certain mechanism, with the hope that it will produce the best decision.…”
Section: Methodsmentioning
confidence: 99%
“…In making decisions there are several difficulties faced, including the various values that are processed, there are factors or criteria that influence the choices available [6], [7]. The process of determining student prescriptions is done for several classes that meet certain criteria including the problem of Multiple Criteria Decision Making (MCDM) [8]- [10] so that the settlement requires a Decision Support System. Another uniqueness of the Decision Support System is that there is a facility that is able to integrate the system installed with the user interactively, known as the dialog subsystem.…”
Section: Introductionmentioning
confidence: 99%
“…Tobiszewski, et al [7] assigned the TOPSIS method to assess the environmental distribution of solvents, so it reported that both alcohols and esters were posed as harmless hydrocarbons in comparison with aromatic hydrocarbons and in the following they have ranged from 1 to 78 chemical groups. Indahingwati, et al [8] applied the TOPSIS procedure based on some criteria such as price, tree size, fruit size, flavor, number of fruits and leaf amount. So obtained results classified 4 kinds of fertilizer based on the aforementioned criteria and ranking system designed to select.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Fuzzy set theory generalised the range values of classical set theory from the integer 0 and 1 to the interval [0, 1]. It was henceforth extended to various forms of fuzzy sets [2]- [5] and has proven to be very useful in many different fields [6]- [9]. However, there are many problems like complete colour characterization of colour images, taste recognition of food items and decision making problems with multi aspects which cannot be characterized by a single membership function of Zadeh's fuzzy sets.…”
Section: Introductionmentioning
confidence: 99%